The Future of Professional Monopolies - Dussault, Gilles (Relations Industrielles / Industrial Relations, 1985)
This paper discusses the future of professional groups in terms of their capacity to retain their dominant position in the division of labour and their monopolistic privilèges in the production system. The sociological literature is briefly reviewed and then it is argued that recent changes within the professions as well as in the context in which they operate, may affect their capacity to retain their present privilèges.